Development of fuzzy logic controller for improved interline unified power quality conditioner. (2nd September 2019) - Yadlapalli, Ravindranath Tagore; Narasipuram, Rajanand Patnaik; Dodda, Anusha
This paper presents the improved interline unified power quality conditioner (iUPQC) and its controlling aspects for nonlinear loads. The nonlinear loads are the major sources of harmonics and raise the power quality issues. However, the iUPQC compensates the harmonics that are generated by a nonlinear load besides reactive power support. This in turn minimises the harmonic distortion both in the source current as well as voltage. Furthermore, it also provides the current and voltage imbalance compensations, reactive power, frequency and voltage support at grid. The simulation of entire power system is fulfilled using proposed FUZZY controller and compared with the conventional PI controller. The performance of both the controllers is sifted in terms of % total harmonic distortion (THD) by considering different case studies having the 3-φ diode rectifier connected to R, RL and RLE loads. The MATLAB/Simulink version R2012b is used for accomplishing the in depth simulation studies.